New Politics Of Race : Globalism, Difference, Justice - Winant, Howard (Book collections on Project MUSE., 2004)
Howard Winant, one of the leading sociologists of race and ethnicity working today, clearly locates race at the crossroads of identity and social structure, where difference frames inequality. The New Politics of Race brings together Winants new and previously published essays to form a comprehensive picture of the origins and nature of the complex racial politics that engulf us today.